2011
DOI: 10.1681/asn.2010070784
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Radiation Exposure from Medical Imaging in Hemodialysis Patients

Abstract: Radiation exposure accompanying medical imaging associates with cancer risk. Patients with recurrent or chronic diseases may be especially at risk, because they may undergo more of these procedures. The aim of this study was to assess the individual cumulative effective doses (CEDs), which quantify radiation from medical imaging procedures, in a cohort of 106 hemodialysis patients during a median follow-up of 3 years. We retrospectively calculated individual radiation exposures by collecting the number and typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…Furthermore, if the presence of detectable calcifications on conventional chest radiographs provides important information, the much higher radiation exposure required for CT scans could be avoided in this population, which already undergoes many diagnostic radiology tests. 14 …”
mentioning
confidence: 99%
“…Furthermore, if the presence of detectable calcifications on conventional chest radiographs provides important information, the much higher radiation exposure required for CT scans could be avoided in this population, which already undergoes many diagnostic radiology tests. 14 …”
mentioning
confidence: 99%
“…Previous studies have reported increased radiation exposure from medical imaging among the general population (7,8). In more recent studies, increased radiation exposure has been identified in hemodialysis patients and posttransplant recipients (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…At the present time, most devices employed to study VC take advantage of electron beam computed tomography (CT) and multislice spiral CT, which allow the physician to assess the development of VC via a quantitative calcium score over time, but do not allow the distinction between intimal and medial calcification [1,2]. However, the primary disadvantages of such techniques are the high risk of radiation exposure for patients [3] and the high cost. Furthermore, the technology can only be employed in specialized medical centers which are not physically capable of providing services to the majority of subjects affected by chronic renal failure.…”
Section: Introductionmentioning
confidence: 99%